Special considerations of determining the gas saturation factor of reservoir rocks of Dnieper-Donets depression gas fields on the basis of petrophysical studies - Poverenniy, Sergey; Lurye, Anatoliy; Chuienko, Oleksandr; Piddubna, Olena (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2022)
Introduction. The gas saturation coefficient is one of the most important parameters for calculating gas reserves. The parameter can be determined by laboratory petrophysical methods applying the residual water saturation coefficient. The latter, in turn, is determined by direct or indirect methods. The direct method is used extremely rarely, while indirect methods are very common - primarily the methods of a semipermeable membrane and centrifugation. The first method is considered the most reliable. Formulation of the problem. When applying the semi-permeable membrane method, the issue of setting the maximum displacement pressure is the key factor that determines the result, as it determines the value of the residual water saturation, and, consequently, the value of the gas saturation coefficient of the reservoir. There are numerous cases when the results of laboratory studies of residual water, and hence the gas saturation coefficient, are clearly discordant with the whole set of geophysical and geological data. This problem is possibly caused by the wrong choice of the laboratory research modes, and specifically, the maximum pressure that is created in the course of the experiment. The research objective is to analyze the ways of setting the maximum water displacement pressures during the experiment in terms of the most reasonable, basic method of a semipermeable membrane; to evaluate their applicability taking into account the best practices and propose their optimal combination for practical work. Previous research. The paper considers various approaches to setting the maximum pressure, including an attempt to model the process of deposit formation, achieving irreducible water saturation, an express method using a centrifuge, determining water-holding capacity, limiting pressures by the size of filter pores, and calculating pressures on the basis of the deposit height. Main material. Two approaches have been distinguished from the considered ones: calculation of the maximum pressure on the basis of the deposit height and calculation on the basis of the maximum pore radius, at which a meniscus can be formed. It is shown that it is rational to combine these two approaches into one, which will allow obtaining more reliable values of the residual water saturation, and hence the gas saturation coefficient. The ultimate maximum displacement pressure for the semi-permeable membrane method, which should be created during the experiment, has been determined. The limiting height of the deposit has also been determined. Any calculation above this parameter does not make sense. The discrepancies between theoretical calculations and actually observed heights of capillary rise and the influence of the layered structure of the reservoir have also been considered. The area of possible practical application of the method has been determined. It is noted that extensive knowledge of the reservoir geometry is crucial for the practical application of the method. Besides, the data on the deposit height should be included in the research proposal. Practical value. The application of the method of calculating the maximum displacement pressure on the basis of the deposit height, taking into account the restrictions on the maximum pore diameters, at which a meniscus can be formed, will certainly increase the reliability of gas reserves calculations in the gas fields of Ukraine.